2007
DOI: 10.1111/j.1440-1746.2007.05071.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and risk factors for gallbladder polyps detected by ultrasonography among healthy Chinese: Analysis of 34 669 cases

Abstract: The prevalence of GB polyps among the Chinese in this study is higher than that reported for other populations. Chinese males and other patients with chronic hepatitis B viral infections have a high risk for developing GB polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
82
3
9

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(116 citation statements)
references
References 27 publications
9
82
3
9
Order By: Relevance
“…Results from Western studies have shown a GBP prevalence of 1.4%-6.9% (10, 14, 15), whereas Asian studies have shown a GBP prevalence of 2.2%-9.5% (1, 16, 17). Such geographic differences may be associated with different genetic and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Results from Western studies have shown a GBP prevalence of 1.4%-6.9% (10, 14, 15), whereas Asian studies have shown a GBP prevalence of 2.2%-9.5% (1, 16, 17). Such geographic differences may be associated with different genetic and environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of GBP peaked in men 30-39 yr of age in both of these periods. In most studies, the highest prevalence of GBP has been observed in the third to fifth decades of life (1, 16). The reasons for peak incidence of GBP in middle aged people are still unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyploid lesions of the gallbladder, which can be found in about 1-5% of adults on ultrasound in Western populations [152,153] and 9.6% in Asian populations [154], are defined as elevations of the gallbladder mucosa. Polyploid lesions of the gallbladder can be true polyps which demonstrate neoplastic changes and may be benign, dysplastic or malignant, or can be pseudopolyps such as cholesterol polyps, inflammatory polyps, or adenomyoma, which are all benign [152,155].…”
Section: Gallbladder Polypsmentioning
confidence: 99%
“…Seventyfour patients underwent sonography, including elastography of gallbladder polyps, in our institution. A polyp was defined on sonography as a lesion attached to the gallbladder wall that was non-shadowing, non-mobile and hyperechoic to bile [5,9]. Patients were included in the study if they had any of the following: sonographic follow-up for at least 2 years, pathology report, or who were diagnosed on the basis of characteristic clinical and radiologic findings.…”
Section: Patientsmentioning
confidence: 99%